Rare Presentation of a Rare Tumor: Histiocytic Sarcoma - Reddivari, Anil Kumar Reddy (Cureus, 2020)
An 84-year-old male, with a large gouty tophus over the left elbow for 20 years, developed a new left elbow area mass about three months ago and presented to the emergency department (ED) with complaints of bleeding from that left elbow area mass after a small blunt injury. Initially diagnosed as olecranon bursitis, it had the worsening size and atypical growth associated with persistent leukocytosis. After being evaluated by multiple specialties, including infectious diseases, orthopedic surgery, and rheumatology, it was decided to do a biopsy, which resulted in the diagnosis of histiocytic sarcoma.